Case report: Peroral endoscopic myotomy for acute pandysautonomia-associated distal esophageal spasm in a child - Zhang, Hanhua; Chi, Biyun; Wang, Fengfan; Shao, Pei; Liu, Huanyu; Fang, Ying (Frontiers in Pediatrics, 2023)
Acute pandysautonomia-associated distal esophageal spasm is a rare disease of unclear etiology. We reported a rare case of acute pandysautonomia-associated distal esophageal spasm in a 12-year-old child who was treated by peroral endoscopic myotomy (POME). The clinical features included recurrent dysphagia, nausea, vomiting, growth retardation, long-term nasal feeding, and signs of autonomic nerve dysfunction, such as decreased tears and sweat, increased saliva. Distal esophageal spasm was patent on full gastrointestinal contrast, endoscopy and high-resolution esophageal manometry (HREM). After POEM, nausea and vomiting disappeared, and dysphagia relieved at two months of follow-up, even though the patient’s neurological problems still existed. POEM is feasible, safe and effective in this case with acute pandysautonomia-associated distal esophageal spasm, with satisfactory short-term clinical responses.